Endobronchial Lipoma: A Rare Cause of Bronchial Stenosis or Obstruction - Jian Chen; Tao Xin; Lei Pan; Yan Li; Weisheng Qian; Jin Wei; Yan Yan; Yan Wang; Faguang Jin; Hua Jiang (Canadian Respiratory Journal)
Endobronchial lipoma (EL) is a rare benign tumor characterized by tracheobronchial smooth-surfaced mass, often resulting in bronchial obstruction without standard guidelines for management. This study seeks to clarify the clinical features and interventions of EL, aiming to improve its diagnosis and outcomes. A retrospective review was conducted on 28516 outpatients treated between January 2015 and December 2019 at the Department of Respiratory and Critical Care Medicine of the Second Affiliated Hospital of Air Force Medical University to collect patients diagnosed with EL. Their clinical, bronchoscopic, chest imaging, and histopathological features along with management were analyzed. Among the patients reviewed, nine were histopathologically diagnosed with EL, comprising seven males and two females. All EL patients exhibited noticeable symptoms, including cough (in eight patients), dyspnea (in six patients), fever (in three patients), expectoration (in two patients), chest pain (in two patients), hemoptysis (in one patient), and fatigue (in one patient). Chest CT abnormalities included endobronchial mass (in four patients), inflammatory exudation (in three patients), atelectasis (in three patients), and infiltration or consolidation (in two patients). In three patients, imaging showed fat density, directly leading to the diagnosis of EL. The EL lesions were distributed with six in the right lung and three in the left lung, all located within the first three subdivisions of the tracheobronchial tree. Treatment approaches varied, with one patient undergoing combined bronchoscopic resection and surgery. The remaining patients received bronchoscopic intervention such as electrosurgical snare resection, argon plasma coagulation (APC), cryotherapy, and holmium laser. Histopathological analysis confirmed the EL diagnosis. Finally, the mass removal restored bronchus patency. Taken together, EL symptoms lack specificity, necessitating reliance on histopathology for EL accurate diagnosis. Bronchoscopic interventions emerge as the preferred option for EL management, surpassing surgical approaches.